Pengaruh Implementasi Model Pembelajaran Group Investigation Dan Learning Cycle 5E Terhadap Prestasi Belajar Agama Hindu Dan Kreativitas Bermain Mind Mapping Siswa Kelas V Sekolah Dasar Negeri 17 Dauh Puri - I Made Dedy Paramartha (Cetta: Jurnal Ilmu Pendidikan, 2021)
Education in Indonesia theoretically emphasized on the success achieved by learners during a learning process. The purpose of education in Indonesia is to create a quality person and character, this research is a research experiment by applying two different models of cooperative learning in students of class V State primary school 17 Dauh Puri in 2016/2017 lesson to find out the difference of achievement study Hinduism and the creativity of students in play mind mapping. The data obtained will be analysed using two methods of data analysis. Anava and manova one way. Anava a road used to measure learning achievement differences of Hindu religion and creativity play mind mapping model of learning the second whereas one way manova is used to analyze the difference of achievement study Hinduism and creativity play mind mapping students simultaneously. The results of testing hypotheses in mind that learning methods are applied affect the learning achievements of the Hindu religion. It proved ultimately based on the acquisition value of the average Hindu learning accomplishments of students who follow the model of cooperative learning group-type investigation is lower than 5E learning cycle model of learning. Simultaneously it is known that the model of cooperative learning group-type investigation and larning cycle 5E influence on hindu learning achievements of students but less effect on students ' creativity in playing mind mapping. Based on the results of the analysis of the effectiveness of the size it is known that learning learning cycle model 5E instructional model and type of group cooperative investigation learning achievements influence on Hindu students learning learning cycle model 5E more influence of Hindu learning achievement grade V. Based on results of testing the effectiveness of learning model is known then the full-size learning cycle 5E more effectively applied at the level of primary school.